SARAJEVO 1914: TRIAL PROCESS AGAINST YOUNG BOSNIA - ILLUSION OF THE FAIR PROCESS - Turanjanin, Veljko; Čvorović, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The authors in the work deal with the trial process against members of the Young Bosnia for the assassination of the Austro-Hungarian heir Archduke Franz Ferdinand and his wife Sophie Chotek in Sarajevo 1914. That issue attends scientific and lay public attention over the hundred years. Authors divided their article into few parts. After the introductory remarks they explain conditions in the country before the assassination, especially problem of the Bosnia and Herzegovina’s annexation and its ratification within the Austro-Hungarian legislation. After that, they remind on the ultimatum that the Dual Monarchy referred to Serbia, which was not accepted, but which “caused” the First World War. The main part of the work is dedicated to the criminal proceeding against the Youngbosnians. They analyze criminal procedure in that time, behavior of the participants, especially president of the judicial council, and defense attorneys, which was shameful, except the defense of the Dr. Rudolf Cistler. Consequently, he had borne numerous negative consequences after the judgment.